The Elgar companion to public choice - Shughart, William F.; Razzolini, Laura, 1960- (Cheltenham : Edward Elgar, 2001)
Provides a thorough account of the public choice approach to economics and politics. The companion joins together the most important issues in the field in a single comprehensive volume. It contains state-of-the-art discussions of both old and contemporary problems, including new work by the founding fathers as well as contributions by a new generation of younger scholars. The book reviews the literature of public choice, highlighting the common ground between all rational choice approaches to politics. It demonstrates the important impact of public choice on economics, political science, philosophy and sociology.
Includes bibliographical references (p. 673-750) and index.
oif 19/02/15
Loan
Keywords: Social choice